Effects of nicotinamide and nilotinib on telomerase activity and telomere length associated with parp-1 regulation in k562 myeloid cell line - Muhammad, Nur Rasyidah (2023)
Chronic myelogenous leukaemia (CML) is one of the four major types of leukaemia disease that affecting myeloid cells. The blast phase of CML has continued to exist as a challenging disease even though the advanced tyrosine kinase inhibitor (TKI) therapy has been introduced, but with its limitations and significantly less effective, causing the patient to be less favourably to respond to the therapy. Switching to highly potent TKI, such as nilotinib also not be able to improve the overall health. Currently, no treatment options are responding effectively in the blast crisis phase of CML. Therefore, it requires an identification of new drug therapies to treat these CML patients. In this study, we investigate the effect of nicotinamide on telomerase activity and telomere length associated with poly (ADP-Ribose) polymerase 1 (PARP-1) regulation in a myeloid cell line to enhance the current treatment of CML as part of the supplementary agent. K562 cell line was used as the model representing CML in the blast phase and was treated with nicotinamide or nilotinib before the combination of both substances was applied. This study has shown the effect of nicotinamide, nilotinib and combination of both substances in exhibit the anti-proliferation ability on the K562 cell line after 48 hours. The implicated mechanism involved in inducing such an effect is not yet clear. In addition of nicotinamide, nilotinib and combination of both substances on the K562 cell line have been indicated as telomerase-positive with significantly higher telomeres activity. Telomere length analysis was evaluated to determine the relation to the function of the telomerase enzyme to maintain the telomere cap of the chromosome. Data showed in longer telomere length in all treatment groups except for nicotinamide with slightly decreases in telomerase activity. The expression of the TERT gene in this study suggests that the effect of these substances on telomerase activity and telomere length is necessarily dependent on their effect on TERT expression. Inhibition of the cell proliferation on the K562 cell line may be associated with the upregulation of PARP-1 related markers (BAX, RIPK1 and TRAF2) and elevated effect in apoptosis assay. The effect of nicotinamide and nilotinib on PARP-1 regulation including mechanisms related to apoptosis, will provide evidence for future and wider research.